Về một thuật toán mô phỏng mô hình tự hồi quy AR(p) - Hòa, Nguyễn Trung (Journal of Computer Science and Cybernetics, 2016)
An algorithm of simulating the regular stationary Gaussian autoregressive model is proposed. Numerical examples have been issued in oder to the efficiency of the algorithm.